1998
DOI: 10.1046/j.1464-410x.1998.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy of the penile portion of the human dorsal nerve of the penis

Abstract: Objective  To determine the distribution of the dorsal nerve of the penis (DNP), the principal somatosensory nerve innervating the phallus, along the penile shaft and within the glans penis. Materials and methods  The DNP was dissected in human autopsy specimens, using low magnification, following the course of the nerve from the symphysis pubis into the glans penis. Results  The shaft and glans were innervated by separate populations of axons. The lateral and ventral portions of the penile shaft were innervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…The EAS branch (or inferior rectal nerve) was easily identified by noting ramifications disappearing into the EAS muscle. In all cats, blunt dissection showed the DPN running inferior to the ipsilateral inferior pubic ramus; in five cats, the dissection was continued distally to show the DPN giving rise to the DNP as it coursed along the dorsal surface of the penis beneath a thick fascia layer analogous to Buck's fascia in the human (Yang and Bradley, 1998c). For the cadaver in which the pubic symphysis was removed, the DPN was also observed sending a branch that innervated the external urethral sphincter (EUS) muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The EAS branch (or inferior rectal nerve) was easily identified by noting ramifications disappearing into the EAS muscle. In all cats, blunt dissection showed the DPN running inferior to the ipsilateral inferior pubic ramus; in five cats, the dissection was continued distally to show the DPN giving rise to the DNP as it coursed along the dorsal surface of the penis beneath a thick fascia layer analogous to Buck's fascia in the human (Yang and Bradley, 1998c). For the cadaver in which the pubic symphysis was removed, the DPN was also observed sending a branch that innervated the external urethral sphincter (EUS) muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous experiment found that percutaneous, transcutaneous, and intraurethral stimulation (monopolar ring electrode) activated the DNP at 3-5 mA, 10-15 mA, and 15-25 mA, respectively [27]. Anatomical observations in humans and cats identified two populations of DNP axons [1,19,28], those travelling laterally on the penile body to the urethra and those travelling down the penile midline to the glans. If these populations play different roles in the inhibitory and excitatory bladder response to DNP stimulation, use of a 3-ring electrode configuration may be valuable for selective activation of the urethral fiber mediated reflex pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The main trunk of DNP is composed of two different populations of axons. 16 The first group traveling along the dorsal midline and terminating in the glans. The other group of fibers radiated from the main trunk over the lateral and ventral aspects of the penile shaft with branches to the corpus spongiosum and urethra.…”
Section: Discussionmentioning
confidence: 99%
“…Genital bulbs are present throughout the glans, but are most numerous in the corona and near the frenulum. Considering the studies of Yang 16 and Halata, 17 injectable implants can be successfully injected into the dermis of glans penis just above the nerve terminal. In this study, injectable HA gel was easily injected into the dermis of glans and effectively decreased the sensory of glans penis.…”
Section: Discussionmentioning
confidence: 99%